Gain-of-function mutations in KATP channel subunits compromise colonic tight junction integrity and epithelial homeostasis in murine models of Cantú syndrome - Maqoud, Fatima; Mallardi, Domenica; Orlando, Antonella; Tricarico, Domenico; Nichols, Colin G.; Antonacci, Marina; Bianco, Giusy; Armentano, Raffaele; Grassi, Ilaria; Valentini, Anna Maria; Russo, Francesco (Frontiers in Medicine, 2025)
IntroductionCantú syndrome (CS) is a rare genetic disorder caused by gain-of-function (GOF) mutations in the KCNJ8 (Kir6.1) or ABCC9 (SUR2) subunits of ATP-sensitive potassium (KATP) channels. CS is characterized by multisystem abnormalities such as cardiovascular defects, hypertrichosis, and skeletal malformations, but its impact on intestinal homeostasis remains poorly understood.MethodsWe investigated the effects of CS-associated KATP channel overactivity on epithelial barrier integrity and tight junction (TJ) proteins using murine models. Heterozygous (SUR2wt/AV) and homozygous (SUR2AV/AV) SUR2(A478V) mutants, as well as Kir6.1(V65M) mice, were studied. mRNA and protein expression of Occludin, Claudin-1, and ZO-1 were analyzed, alongside histological and immunohistochemical assessments. Markers of apoptosis and survival, including caspase-3 activity and BCL2/BCL2L1 expression, were also evaluated.ResultsGOF mutations in KATP channels caused significant dysregulation of TJ proteins. Occludin expression was increased in SUR2AV/AV mice but decreased in SUR2wt/AV and Kir6.1 mutants, while Claudin-1 and ZO-1 were consistently reduced across all models. Immunohistochemistry revealed disrupted TJ localization and reduced apical junctional integrity. Histological analyzes showed epithelial disorganization, smooth muscle hypertrophy, fibrosis, and inflammatory infiltration. These alterations were accompanied by increased caspase-3 activity and reduced BCL2 and BCL2L1 expression.DiscussionOur findings demonstrate that CS-associated KATP channel GOF mutations disrupt tight junction dynamics and induces structural remodeling of the colon. This establishes a novel link between KATP channel dysregulation, metabolic-epithelial interactions, and intestinal pathophysiology in CS. Furthermore, the results highlight potential therapeutic targets to mitigate barrier dysfunction, providing a basis for developing interventions to address gastrointestinal symptoms in CS.